The Investigation of University Students Knowledge and Behaviors About Rational Drug Use (Turkey Health Literacy Journal, 2022)
The Problem of The Research: Adherence to treatment decreases, drug interactions, and the frequency of adverse reactions increase due to the principles of rational drug use are not followed by the public. The Aim of The Study: This study aimed to evaluate the knowledge and behaviors about the rational drug use of Medicine, Pharmacy, Health Management, and Nursing students who receive health education. Method: The snowball sampling method was used in this descriptive study. A total of 749 students from the departments of Medicine, Pharmacy, Nursing, and Health Management who agreed to participate in the study were asked to answer 36 questions online. Statistical Package for Social Sciences (SPSS), version 22.0 for Windows (SPSS Inc. Chicago, USA) computer package program was used for statistical analysis of the data. In the descriptive statistics section, categorical variables are given as numbers and percentages, and continuous variables are presented as mean ± standard deviation and median (smallest – largest value). Conformity of continuous variables to normal distribution was evaluated using visual (histogram and probability graphs) and analytical methods (Kolmogorov Smirnov/Shapiro-Wilk tests). Chi square test was used in the comparison analyzes of categorical variables. In this study, the statistical significance level was accepted as p<0.05. Results: Of the individuals participating in the study, 29.2% are in Health Management, 26.7% in Pharmacy, 22% in Medicine, and 22% in Nursing students. 81.4% of the participants are women. There is a statistically significant relationship between the usage of medication with a recommendation of a neighbor or close relative, and the act of prescribing medication, even if it is not necessary (p=0.006). There is a statistically significant relationship between buying a drug from the pharmacy without a doctor’s examination and the act of prescribing medication even if it is not necessary (p<0.001). There is a statistically significant relationship between the action taken when the drug has a side effect and the situation of prescribing the medication even if it is not essential (p=0.020). In cases where the complaint does not go away, there is a statistically significant relationship between taking medication without the recommendation of a physician and prescribing medication even if it is not necessary (p=0.019). Conclusion: It is seen that among the drugs used without consulting a physician, painkillers take the first place with a huge difference. Another important issue is that although the rate of drug use by the students in this study without consulting the physician is low, attention should be paid to the duration of use of the drugs prescribed by the physician.